Thirsty for Change: Considering Water Privatization in Developing Countries - Ruben-Samala, Celene (Consilience, 2008)
Access, maintenance, and distribution of clean water are daunting tasks for developing nations. Efforts to provide clean drinking water have often fallen short, which has prompted the World Bank to advocate for privatization. From a theoretical perspective, privatization blends the advantages of corporate efficiency with responsible management on behalf of the national government. Analysis of attempts to privatize water in the Philippines, with the establishment of the Metropolitan Waterworks Sewerage System (MWSS), shows mixed results. Between 1997 and 2003, citizens with access to water increased from 58 percent to 84 percent, yet water became five times costlier due to privatization. Advocates may applaud the efficiency of the model, but developing nations must emphasize accessibility and affordability of the resource. Privatization, as a model for water distribution, remains contentious.